Rapid and high-efficiency generation of mature functional hepatocyte-like cells from adipose-derived stem cells by a three-step protocol. Issue 1 (December 2015) - Xu, Fen; Liu, Junli; Deng, Jie; Chen, Xiaolei; Wang, Yuan; Xu, Pengchao; Cheng, Lin; Fu, Yanli; Cheng, Fuyi; Yao, Yunqi; Zhang, Yujing; Huang, Meijuan; et al.
Abstract The generation of functional hepatocytes is a major challenge for regenerative medicine and drug discovery. Here we show a method that facilitates generation of induced functional hepatocytes (iHeps) from adipose-derived stem cells (ADSCs) within 9 days. iHeps express hepatocytic gene programs and display functions characteristic of mature hepatocytes, including cytochrome P450 enzyme activity. Upon transplantation into mice with carbon tetrachloride (CCl4 )-induced acute fulminant liver failure, iHeps restore the liver function and prolong survival. The work could contribute to the development of alternative strategies to obtain nonhepatic cell-derived mature hepatocytes with potential for biomedical and pharmaceutical applications.